047 Clinical outcome and sensitive troponin I assay in patients with suspected acute coronary syndrome. (22nd September 2015) - Mills, N L; Churchhouse, A M D; Anand, A; Gamble, D; MacLeod, M; Graham, C; Walker, S; Denvir, M A; Fox, K A A; Newby, D E
Abstract : Background: Troponin assays have evolved and become increasingly sensitive. The prognostic value of identifying small elevations of plasma troponin concentrations in patients with suspected acute coronary syndrome remains uncertain. Methods: We performed a retrospective observational study of 1038 consecutive patients admitted with suspected acute coronary syndrome during the validation of a sensitive troponin I assay. Patients were stratified into three groups based on plasma troponin concentrations: <0.05, 0.05–0.19 and ≥0.20 ng/ml. During this validation phase, only concentrations above the previous diagnostic threshold of ≥0.20 ng/ml were reported to clinicians. Results: Plasma troponin concentrations were <0.05 ng/ml in 657 (63%), 0.05–0.19 ng/ml in 90 (9%) and ≥0.20 ng/ml in 291 (28%) patients. In comparison to patients with a troponin concentration ≥0.20 ng/ml, those with a concentration of 0.05–0.19 ng/ml were less likely to be referred to a cardiologist (44 vs 93%), to receive dual anti-platelet therapy (27 vs 80%), or to undergo coronary revascularisation (17 vs 59%) (p<0.001 for all). At 1 year, patients with troponin concentrations of 0.05–0.19 ng/ml had worse clinical outcomes than patients with troponin concentration of <0.05 ng/ml or ≥0.20 ng/ml (Abstract 47 Figure 1 ; p<0.001). Conclusions: In patients with suspected acute coronary syndrome, use of a sensitive troponin assay markedly increases the incidence of myocardial infarction and identifies those at high-risk of reinfarction and death. Its use will lead to major changes in practice with the potential for reduced morbidity and mortality.